Effectiveness of Peer Group Education on Adolescents to Improve the Behavior of Prevention of Cervical Cancer - Dina Isfentiani; K Kasiati (Alliance oh Health Activists (AloHA), 2018)
Cervical cancer is a female reproductive disease, and is the most common cancer in the world. Knowledge about prevention of cervical cancer can be disseminated especially through the formation of adolescent peer groups. The purpose of this study was to determine the effectiveness of education using the peer group adolescent method to improve the prevention behavior of cervical cancer, in the “Taruna Pembangunan Surabaya” Intensive High School, with the design of the Non Equivalent Control Group. Respondents of the study were 90 students of the XI grade of “Taruna Pembangunan Surabaya” Intensive High School who were selected by simple random sampling technique. Data were collected through filling in questionnaires, then analyzed using T test and Manova. Based on the results of data analysis, it was concluded that prevention of cervical cancer using the peer group method in the Surabaya Midshipman Intensive High School was not yet effective. There were no differences in behavior between the treatment and control groups. Keywords: Cervical cancer, HPV immunization, Peer group education